The Effect Of Group Guidance Using Discussion Techniques To Improve Reproductive Health Understanding In Generation Z - Welna, Amalia Maulidina; Nurwahyuni, Nurwahyuni; Wahyuningsih, Nur Eka; Diniy, Muh Yusran (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2026)
Generation Z, especially adolescents, face problems of lack of knowledge about reproductive health, which can lead to risky behavior, unplanned pregnancies, and sexually transmitted infections. This condition is exacerbated by the prevalence of false information on social media and the lack of reproductive health education in religious schools. This study aims to determine the effect of group counseling using discussion techniques on the understanding of students at MA Muhammadiyah Palu. Using a quantitative approach with a one-group pretest-posttest experimental design, the study involved 10 students aged 15–18 years who were selected purposively. The instrument was a valid and reliable comprehension test, analyzed using descriptive statistics and inferential analysis, which included the Wilcoxon test and effect size. The results showed a significant increase (Z = -2.809; p = 0.005 < 0.05) with Cohen's d = 2.47, which is classified as a very large effect. Thus, group counseling using discussion techniques is effective in improving adolescents' understanding of reproductive health in religious schools. Keywords:Adolescent Health; Counseling; Group Guidance; Generation Z; Reproductive Health.